Rational design of NiFe alloys for efficient electrochemical hydrogen evolution reaction: effects of Ni/Fe molar ratios. Issue 45 (12th October 2022) - Messaoudi, Yazid; Belhadj, Hamza; Khelladi, Mohamed R.; Azizi, Amor
Abstract : Developing and designing high-performance and stable NiFe electrodes for efficient hydrogen production in alkaline medium. Abstract : Developing and designing high-performance and stable NiFe electrodes for efficient hydrogen production are the greatest challenges in electrochemical water splitting. In this work, NiFe alloys with different Ni and Fe contents are prepared by a simple electrodeposition method using different molar ratios of Ni/Fe precursors (Ni/Fe; 1 : 3, 1 : 1 and 3 : 1). The obtained NiFe electrode with a molar ratio of 3 : 1 exhibited better electrocatalytic activity for the HER than the other NiFe electrodes with 1 : 3 and 1 : 1 molar ratios. The NiFe (Ni/Fe, 3 : 1) electrode required an overpotential of 133 mV to reach a current density of 10 mA cm −2, which was much lower than those of NiFe with molar ratio of 1 : 3 (220 mV), and 1 : 1 (365 mV), respectively. Tafel slope analyses demonstrated that the HER mechanism of NiFe alloy coatings followed the Volmer reaction type. The superior electrocatalytic performance of the NiFe alloy for HER depending on precursor molar ratio of Ni/Fe was attributed to their composition in terms of Ni and Fe content, structure and surface morphology. Specifically, the electrodeposition of the NiFe alloy was obtained in a molar ratio Ni/Fe, 3 : 1, and induced the formation of NiFe layered double hydroxide (LDH) with a nanosheet-array structure. The high electrocatalytic activity of NiFe LDH (Ni/Fe, 3 : 1) confirmed the critical influence of Ni and Fe contents in the alloy resulting in an increase the active surface on the surfaces, which is most likely explained by the higher surface roughness and the low crystallinity structure of NiFe nanosheet-array, supported by ECSA measurement, XRD, SEM and AFM analyses. The present strategy may open an avenue for developing cost-effective, stable and high-performance electrocatalysts as advanced electrodes for large-scale water splitting.